Flashcards for English Vocabulary Mastery in Indonesian Junior High School: A Systematic Review - Ani Sumarni; Siti Hadianti; Henri Setiawan; Salah Khlief Almotairi (PT. Global Research Collaboration, 2026)
The purpose of this systematic review was to gather data on the effectiveness of flashcards in improving junior high school students' English vocabulary mastery. Studies were selected using pre-established inclusion criteria focusing on quasi-experimental and experimental designs after a thorough literature search across various academic databases. A total of seven papers were included in this evaluation because they met the eligibility requirements. The results indicated that students' vocabulary learning outcomes consistently improved with the use of flashcards, both digital and traditional. However, the magnitude of effectiveness varies depending on instructional design, learner characteristics, and implementation strategies, particularly those involving retrieval practice and spaced repetition. Digital flashcards tend to offer additional advantages such as flexibility and increased learner engagement, while traditional flashcards remain effective in structured classroom settings. Despite these positive findings, the evidence is limited by methodological constraints, including quasi-experimental designs and a focus on short-term learning outcomes. Overall, flashcards represent an effective instructional strategy for vocabulary acquisition, although their impact is highly dependent on how they are implemented. Future research should focus on long-term retention and more rigorous experimental designs to strengthen the evidence base.